Mutational screening of exon 1 of smad7 in Malay patients with ventricular septal defect - Hashim, Hashima (2015)

(untitled)
Congenital heart disease (CHD) affects approximately 8 in every 1000 live births with ventricular septal defect (VSD) being the most common phenotype. VSD is thought to arise from genetics and environmental factors, however most of the causes remain unknown. It was hypothesized that SMAD7 gene could influence the risk of VSD. SMAD7 is a potent antagonist of TGF-signalling pathways and has been found to be involved in embryonic cardiovascular development in mouse models. However, its role in the pathogenesis of VSD in human has yet to be fully understood. Therefore, SMAD7 gene was examined in for its susceptibility to VSD in this study. A case-control study was conducted to examine whether SMAD7 is associated with VSD in Malay population. Exon 1 of SMAD7 which encodes the functional MH1 domain was re-sequenced in 30 non-syndromic VSD patients and 30 control individuals. One common upstream gene sequence, rs7236774 and one rare synonymous sequence, rs368427729 were observed in both cases and controls. Further analysis on these two variations did not show any statistically significance association with the risk of developing VSD. In conclusion, this study has indicated that the exon 1 of SMAD7 was not associated with VSD in Malay population. However, these findings could have been limited by small sample size. Therefore, further study in a larger cohort is warranted to yield a concrete evidence of this association.